Effect of academic-environmental stress on apical periodontitis of non-endodontic teeth - Zainab Shakir Amory; Hashim Mueen Hussein; Aya Nashwan Naji; Mustafa Tariq Mutar (Medical Journal of Babylon)
Abstract Background: The periapical area of a tooth was diagnosed using radiography; many types of risk factors can affect the health of the apical area which is the stress during life. Objective: To analyze the prevalence of academic-environmental stress and apical periodontitis in non-endodontic teeth of dental students using cone-beam computed tomography (CBCT) X-ray, and to demonstrate the association between stress and the prevalence of apical periodontitis. Materials and Methods: Cross-sectional study was done on the 103 recruited dental students aged 22–24 years during the final examination year of study in dentistry college. The academic-environmental stress scale was used to measure the level of stress in each student. The CBCT X-ray was taken for each student. The apical area was measured only for non-root canal-treated teeth using the CBCT periapical radiography index. Chi-square (χ2) test was used to show the percentages of stress and the relationship between apical periodontitis and stress in students. Results: 53 students (51.5%) had a stressed state, whereas 50 students (48.5%) had a non-stressful state. The prevalence of apical periodontitis was greater among stressed than that of non-stressed students in non-endodontic teeth. Statistically, there was a significant relationship between academic-environmental stress and apical periodontitis in non-endodontic teeth. Conclusion: There was a negative effect of examination stress on the apical healthy of teeth that can be increased with the presence of any additional factors such as problems of life.